Perbandingan Metode Cooperative Learning Tipe Numbered Heads Together (NHT) dengan Metode Inquiry Learning pada Mata Pelajaran Matematika di Kelas IV SDN 01 Rensing - Yuliana Susanti (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
The purpose of this study was to determine whether there were differences in learning achievement by using the Cooperative Learning method type NHT with the Inkuiry Learning method on grade IV math subjects SDN NO 01 Rensing. This research was conducted by sample research where the sample from this study was class IV which consisted of Class IV-B and IV-C which numbered 56 people consisting of 30 men and 26 women. In this study divided into NHT type Cooperative class consisting of 28 students (IV-B) and Inkuiry class consisted of 28 students (Class IV-C) with the provisions of the learning experiment class using the NHT type Coperative Learning method while the learning control class by using the Inkuiry Learning method. After doing the research, the highest value of 96 and the lowest value of 40 for the NHT type Cooperative class is highest, while the highest value is 100 and the lowest value is 36 for the Inkury class.After the results of the research data are processed, the average value for the NHT type Cooperative class is 69.43 with a standard deviation of 15.16 while the Inkuiry class average is 64.18 with a standard deviation of 19.66. Thus learning using the type of Cooperative Learning method including NHT high category while learning using the Inkuiry Learning method including the medium category. So it can be concluded that there are differences in learning achievement using the Cooperative Learning method type NHT by using the Inkuiry Learning method on mathematics subjects in class IV SDN NO 01 Rensing.